Mengoptimalkan Kecerdasan Anak Melalui Metode Bermain - Safitri, Ika Nur (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
One of the extraordinary gifts from God to humans is intelligence. This gift is given free of charge so that humans can become His representatives or khilafah on earth so that they can manage their lives well. Based on intelligence potential, every human being actually has the potential to become a genius. Intelligence is a person's ability to solve the problems they face. As parents who really love their children, of course they have a great and noble responsibility to be able to develop the intelligence in their children that has been given by God. Forming intelligent and creative children is the duty and obligation of all parents. This task is actually not difficult. One way to make children smart and creative is by playing. Play activities give children experience dealing with problems and viewing them as exciting challenges. In a child's life, play has an important meaning. It can be said that every healthy child always has the urge to play so it can be ascertained that children who do not play are generally sick, both physically and spiritually. So, games and activities can create intelligence and creativity.